Ketepatan Waktu Pengembalian Berkas Rekam Medis Berdasarkan Unsur-Unsur Manajemen Di RSU Bina Kasih Medan Tahun 2021 - Johanna Christy; Siti Suarni Waruwu (Akademi Perekam dan Informasi Kesehatan Imelda, 2023)
Management is a process consisting of regulatory, planning, organizing, directing and controlling activities carried out to determine and achieve goals through the use of human resources and other resources to achieve organizational goals effectively and efficiently. Elements of management include 5M including (Man, Method, Material, Machine, Money). The purpose of this research is to determine the 5 element of The Timely Return of Inpatient Medical Record Files at Bina Kasih Hospital in 2021. This type of research is qualitative with a case study approach. The research was conducted in August-September 2021 which coincided with Bina Kasih Hospital in Medan with 7 subjects and head of medical record informants, the sampling technique used was purposive sampling. The timeliness of returning inpatient medical record files in August 2021 totaled 270 files and the number of inaccuracies in inpatient medical record files was 60.74% machine and money elements.